Evaluación de los servicios ambientales del bosque urbano “Caja de Agua” (Lima, Perú) mediante i-Tree Eco y i-Tree Canopy - Huaman, Rosa (2024)
The objective of this study was to evaluate the "Caja de Agua" urban forest of 3.06 ha located in the district of San Juan Lurigancho in the province of Lima, Peru, using the i-Tree Eco and i-Tree Canopy programs. A forest census was conducted in the study area in which all tree and arborescent individuals with a diameter at breast height (DBH) greater than 2.5 cm at 1.30 m from the ground were measured. In total, 765 individuals were recorded, grouped into 43 species, 40 genera and 22 botanical families. With the i-Tree Eco program, the environmental services provided by the "Caja de Agua" trees were estimated, which were the elimination of 256.9 kg/year of air pollutants (CO, O3, SO2, NO2, PM2.5 and PM10), the annual capture of 16.44 metric tons of carbon, the storage of 172 metric tons of carbon and the production of 43.83 metric tons of oxygen per year. It was determined that the forest species that provided the greatest environmental services were Eucalyptus camaldulensis Dehnh., Ligustrum lucidum W.T. Aiton, Fraxinus americana L. and Ceiba speciosa (A. St.-Hil.) Ravenna, influenced by their abundance and leaf area. The i-Tree Canopy program was used to classify four types of cover in the "Caja de Agua" urban forest (arboreal/shrub, bare soil, herbaceous and constructions) by photointerpreting satellite images available in Google Earth, which determined that there has been a decrease in tree cover in the last 14 years. The results indicate that the "Caja de Agua" urban forest provides environmental services for the city, which should be conserved for the benefit of the local community.